The effects of adding lactococcal proteinase on the growth rate of Lactococcus lactis in milk depend on the type of enzyme. - Helinck, S (1997)
Increasing the proteolytic activity of Lactococcus lactis cultures in milk by adding the corresponding proteinase resulted in a stimulation of the growth rate regardless of the strain and the type of proteinase, demonstrating that the rate of casein degradation was responsible for the growth rate limitation of L. lactis in milk. However, the stimulation was only transient, and the reduction in growth rate in the poststimulation phase depended on the type of cell envelope proteinase. When a PI-type proteinase was added, three causes were involved in the subsequent reduction in growth rate: degradation of the added proteinase, repression of the proteolytic activity expressed by the cells, and competition for peptide uptake. When a PIII-type proteinase was added, the cessation of stimulation was due to the autoproteolysis of the added enzyme only.